EFFICACY AND SAFETY OF ACCELERATED DIAGNOSTIC PROTOCOL USE IN PATIENTS WITH SUSPECTED ACUTE CORONARY SYNDROME - O. V. Baturina; S. R. Gilyarevsky (Рациональная фармакотерапия в кардиологии)
The use of modern accelerated diagnostic protocols in patients with suspected acute coronary syndrome is discussed. Evidence base that can give occasion to selection of acceptable accelerated diagnostic protocol for safe exclusion of acute myocardial infarction early after seeking medical attention is presented. Advantages and disadvantages of certain protocols are discussed.